Find the sum of the following series :-
1 . 3 1 4 + 3 . 5 2 4 + 5 . 7 3 4 + . . . . . . . . . . + T n
=> Here u.v denotes u*v.
=> Find the sum of first 12 terms.
=> The answer can be expressed in the form of b a where a and b are co-prime integers. FIND a + b.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Sir can you suggest something by which we can get a clicking.. How we can break such series in a simpler way?
Log in to reply
Sorry to say, I wish I could. But I think each problem has its unique way of solving. There may not be a generalization which we hope for. Anyway, I am not that good actually. I worked out the answer with a spreadsheet, after all there were 12 terms to add up with. Then I looked through to see how I could best write the solution. It just that I have patience being a retired person.
Log in to reply
So. I must ask. That what is. The first ques. That arises in your mind when you see such series?
Log in to reply
@Rahul Chandani – I first use telescopic method. Then later I notice the summation can be broken down in three parts ∑ n 2 , ∑ 1 and the last some we can use telescopic. A perfect question to text knowledge in series.
Log in to reply
@Chew-Seong Cheong – Okkaayy! Thank you sirr! :)
Problem Loading...
Note Loading...
Set Loading...
n = 1 ∑ 1 2 ( 2 n − 1 ) ( 2 n + 1 ) n 4 = n = 1 ∑ 1 2 4 n 2 − 1 n 4 = n = 1 ∑ 1 2 4 n 2 − 1 n 2 ( n 2 − 4 1 ) + 4 1 n 2
= n = 1 ∑ 1 2 4 n 2 − 1 n 2 ( n 2 − 4 1 ) + 4 1 ( n 2 − 4 1 ) + 1 6 1
= n = 1 ∑ 1 2 4 n 2 − 1 4 1 n 2 ( 4 n 2 − 1 ) + 1 6 1 ( 4 n 2 − 1 ) + 1 6 1
= 4 1 n = 1 ∑ 1 2 n 2 + 1 6 1 n = 1 ∑ 1 2 1 + 1 6 1 n = 1 ∑ 1 2 4 n 2 − 1 1
= 4 1 ( 6 1 2 ( 1 3 ) ( 2 5 ) ) + 1 6 1 ( 1 2 ) + 1 6 1 n = 1 ∑ 1 2 2 1 ( 2 n − 1 1 − 2 n + 1 1 )
= 4 3 2 5 + 4 3 + 3 2 1 ( n = 1 ∑ 1 2 2 n − 1 1 − n = 2 ∑ 1 3 2 n − 1 1 )
= 4 3 2 5 + 4 3 + 3 2 1 ( 1 1 − 2 5 1 ) = 4 3 2 5 + 4 3 + 1 0 0 3 = 2 5 4 0 8 2 = b a
⇒ a + b = 4 1 0 7